Perancangan Interior Planet Cinema di Kabupaten Bone dengan Pendekatan Eko-Interior - Sabrina Versiska Gosang; Yusita Kusumarini; Meirina Kuncahyowati (Intra, 2019)
In Bone district, infrastructure in entertainment sectors are being built and developed. One of the entertainment sectors development currently underway is Planet Cinema. Planet Cinema is a cinema built with modern architectural forms and environmentally friendly building concepts. The Environmentally Friendly Concept in Planet Cinema provides a new atmosphere for the community. The cinema building is expected to be an example of an eco-friendly building icon in Bone and surrounding districts. To support the design of Planet Cinema buildings, the interior is designed according to the architectural design. Planet Cinema interior design is made effective and efficient according to the flow of user activity. In addition, to support the concept of environmentally friendly buildings, interior design is also carried out with the approval of Eco-Interior. Aspects of Eco-Interior will be used as conceptual ideas in the principles of applied analysis in the design process of Planet Cinema. The design method used is Design Thinking with stages consist of, understand, observe, point of view, ideate , prototype , test , storytelling, pilot, and business models. Planet Cinema's interior design is expected to be used as a means of recreation, educative, and appreciative for the public while enjoying the modern cinema facilities with a different design concept from other buildings that have ever been around. The ongoing design of Planet Cinema's interior is also expected to support Bone district to start a modern infrastructure while supporting environmentally friendly buildings.